Knockdown of igf3 gene by RNA interference causes gonadal development inhibition of common carp (Cyprinus carpio). (4th February 2021) - Song, Feibiao; Wang, Lanmei; Yu, Zhenzhen; Zhu, Wenbin; Fu, Jianjun; Dong, Zaijie
Abstract: RNA interference is an important method in studying the gene function of organisms. As a novel important gene in gonadal development of teleost fish, the function of igf3 is worth of researching. In this study, the igf3b ‐dsRNA of C. carpio was successfully synthesized, and long‐term igf3 interference experiments were conducted. Intraperitoneal injection of igf3b ‐dsRNA could influence the serum sex hormone level and significantly reduced the expression level of insulin‐like growth factors (IGFs) in hypothalamic–pituitary–gonad (HPG) axis. After a 60‐day interference experiment, igf3 knockdown could affect the development of ovary and testis of juvenile C. carpio . These findings show that igf3 knockdown may have a negative effect on gonadal development of C. carpio through HPG axis.